(untitled) (NAU Journal of Technology and Vocational Education, 2024)
This study sought to assess the tele-communication and media competencies possessed by OTM lecturers in tertiary institutions in Anambra and Enugu states. The study adopted a descriptive survey design. Two research questions guided the study while two hypotheses were tested at 0.05 level of significance. The population consisting of 38 OTM lecturers was studied. A validated questionnaire with reliability coefficients of 0.71 and 0.84 was used for data collection. The arithmetic mean and standard deviation were used to analyze the data in respect of the research questions while ANOVA was used to test the hypotheses. It was found that respondents possessed both tele-communication and media competencies at a low extent. The researchers’ conclude that the respondents can hardly produce graduates with tele-communication and media competencies. It is recommended, among others, that management of Polytechnics should provide adequate technological resources, technical and administrative support to encourage OTM lecturers to successfully use ICT in classrooms.